Establishment of a survival rabbit model for laryngotracheal stenosis: A prospective randomized study - Wei Chen; Qingyu Wang; Hongming Xu; Yuhui Xie; Lina Zhang; Yao Li; Guofeng Yan; Yiwen Ding; Shunkai Lu; Zhibo Xie; Jiarui Chen; Mengrou Xu; et al. (Laryngoscope Investigative Otolaryngology)
Abstract Objective To develop a reproducible survival rabbit model for laryngotracheal stenosis (LTS). Methods Seventy New Zealand white (NZW) rabbits were randomly divided into experimental groups (n = 30) and a control group (n = 40). In experimental groups, a nylon brush was inserted retrograde from the tracheotomy through the subglottis and rotated until a full layer circumferential mucosal injury to cartilage exposure, assisted by fiberoptic laryngoscopy (FOL) visualization. Experimental group 1 (n = 10), rotated 10 times; group 2 (n = 20), rotated 20 times. The control group underwent tracheotomy only without nylon brush scraping. The rabbits underwent FOL at 1st, 4th, 8th, and 12th week postinjury respectively to observe the formation of LTS. They were euthanized and the larynxes and tracheas were subjected to gross and histopathological examination at 12 weeks postinjury. Results The control group all survived, while five cases in experimental groups died from LTS and/or mucous plug. Histological observation showed that the control group had intact laryngotracheal mucosal epithelium without any stenosis; the experimental groups showed proliferation of fibroblasts and thickening of collagen fibers. The mean stenosis in control group was 9.31 ± 0.98%, while that in experimental group 1 was 32.78 ± 7.07% and 58.25 ± 8.96% in experimental group 2. The difference between the three groups was statistically significant (χ2 = 47.98, p < .05). Conclusions We successfully developed a reproducible survival rabbit model for LTS using a nylon brush through FOL visualization combined with tracheostomy. This model can provide a mature and stable animal model for the exploration of wound‐healing pathophysiology and the effect of interventions. Level of evidence NA.